Sub-supplier management approaches in the context of modern slavery – The cases of the construction and food industries - Hess, Christin (2017)
The Ethical Trading Initiative (2017) and the International Labour Organisation (2017) claim that 21 million people live in slavery today. This phenomenon, called modern slavery, mainly occurs beyond tier one of corporate supply chains. However, there is only little research on the concept of modern slavery through the lens of multi-tier supply chain management. As a result, this research aims to explore sub-supplier management approaches in the context of modern slavery. As such, due to their relevance in this field, the two case studies of the food and construction industry were chosen to be analysed in more detail. For this purpose, primary data was collected through semi-structured interviews with relevant players in these two industries. In addition, secondary data in form of other primary research interviews and various online sources supplemented the data collection. The research found major differences between the two case studies. Whereas the food industry mainly uses the three management approaches, namely direct, indirect, and collaboration, the construction industry merely focusses on the indirect approach. The research could further reveal major contingencies that explain these strategic choices, as well as enablers that support the implementation of these approaches